Environmental Risk Analysis In Handling Medical Waste At Puskesmas Lubuk Begalung Kota Padang Using Environmental Risk Assessment (Era) - Ahmad Hadian Pratama Hamzah; Aubrey Ridha Hadyana; Nurhasanah Nurhasanah; Subekti Nurmawati (Universitas Pahlawan Tuanku Tambusai, 2023)
Puskesmas is one of the health service facilities that are useful for improving the degree of public health. Health service activities are carried out by providing health protection to the general public, patient safety, a good health facility environment, and human resources experts at these health facilities. In order not to interfere with the operational activities of health facilities in serving health, an environmental risk management is needed in order to avoid environmental pollution that can come from infectious diseases that are easily found in these health facilities. One source of environmental pollution that can be found from health facilities is waste, especially medical waste, which is included in the class of waste that can harm the environment (biohazard) so that the waste also requires special handling for its management. The variables used in the study were the actions of officers in medical waste management, infrastructure facilities in processing medical waste, the level of knowledge of officers in managing medical waste, the duration of time used in medical waste management, and the volume of medical waste produced in a certain duration of time.